Los procesos de liberalización y privatización de los servicios públicos económicos en el Perú - Cairampoma Arroyo, Alberto (2023)
This article deals with the processes of liberalization and privatization of economic public services within the framework of the social market economy in Peru. The meaning of liberalization and privatization is provided to differentiate their scope and differences, to later explain how processes have been applied in Peru, particularly in the public services of telecommunications, electricity, natural gas, and potable water and sanitation.